Student learning style in vocational higher education - Auliana Nasution; Ambiyar Ambiyar; Wakhinuddin Simatupang (invotek, 2021)
When student learning styles are known, teaching can be designed according to student interests through teaching strategies, teaching methods and techniques, and selecting and applying the necessary teaching tools. This research aims to describe vocational students' learning styles using Forster learning styles and investigate the relationship between these learning styles and mathematics learning achievement. Researchers analyzed vocational students' mathematics learning styles using the "How Do I Learn?" developed by Forster. By using a screening model and quantitative research methods, data collected. The collected data from the instrument containing questions related to the student's mathematics learning style are then processed using SPSS, analyzed using descriptive statistics and one-way analysis of variance (ANOVA). Descriptive statistics were applied to view participant demographics and an overview of each learning style score, while one-way analysis of variance (ANOVA) was conducted to assess differences in mathematics learning styles among students based on mathematics scores. The results showed no relationship found between reflective, curious, diligent, and user learning styles using the questionnaire developed by Foster and the students' mathematics scores.